FOUNDATION AND DEEP EXCAVATION DESIGN SURAKATA GREAT MOSQUE - Arya Faviandhana, Reyhan
Surakata Great Mosque is a 5-story building with 3-story basement used for parking area located in Surakarta. The design of foundation must meet the design criterias which are load-carrying capacity and settlement. The type of foundation used is bored-pile foundation with the depth of 21 meters and the diameter of 1 meters. The single pile axial bearing capacity was determined by manual calculation using Meyerhof method, the single pile lateral bearing capacity was determined using LPILE, and the group pile axial bearing capacity was determined using GROUP alongside manual calculation using paku keling method. On the other hand, the analysis of group pile elastic settlement was done by manual calculation using Vesic method while the analysis of group pile consolidation settlement was done by using 2:1 stress distribution method. The analyses altogether resulted in seven group pile configurations and a total of 260 piles. Deep excavation design for the need of basement area of Surakarta Great Mosque with the depth of 9 meters is supported by diapraghm wall system and ground anchors. The analysis is done in PLAXIS2D with hardening soil model material. The depth of penetration is 20 meters and the thickness is 0,6 meters. Deep excavation is divided into three construction stages with 4 meters excavation for the first two step and 1 meters excavation for the last one. Dewatering to lower ground water level to 1 meter below excavation base. Three ground anchors are installed at the elevation of -3,5 meters and -7,5 meters with prestressed force assigned after each stage of excavation.